Personalized Shopping Experiences: The Unexplored Potential Of AI Enhanced Personalized Consumer Journey (International Journal of Environmental Sciences, 2025)
AI introduces dual benefits to modern retail because it enables radical shopping experience upgrades through giving customers what they expect regarding personalized precision and automated service. AI applications already enhance retail operations through recommendation engines and price optimization systems as well as conversational AI tools but there exists massive opportunity to employ AI toward building customized emotive and tailored shopping paths for consumers. The paper argues for retail companies to implement AI as a strategic tool that can bridge online-offline sales, understand consumer needs, and establish genuine emotional connections with their customers. The current adoption of AI faces significant hurdles because online and offline business operations lack proper integration. Users expect to experience uninterrupted and uniform customer preferences throughout all their touchpoints. Through AI applications companies can place separate communication channels under one synchronized domain through the consolidation of multiple information sources into detailed consumer profiles. AI smart mirrors utilize customer online wish lists to provide recommendations while geofenced technology sends alerts about exclusive retail items present in the local area. Nike and Sephora joined forces to present successful approaches for developing uninterrupted shopping activities that adapt to consumers' surrounding contexts. Something that many people tend to miss is AI adapting to human feelings. With the incorporation of natural language processing, facial recognition, and biometric sensors under affective computing, it is now possible for AI to notice faint emotional cues and adjust AI-human interaction for maximum comfort. However, these concerns need to be solved first: privacy, ethics, and other concerns. Therefore, it can be concluded that the retail sector is optimistic for the future. Their main concerns rest on AI learning to go beyond dealing with mere transactions and focusing on building an emotional and personal bond with the user, thus creating a connection that is effortless. This study aims to illuminate the solutions for technical ethical and organizational problems and commend empathy and trust as the main drivers of the defining approach that needs more focus.